2021
DOI: 10.1098/rsbl.2021.0038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of marine heatwaves for sea turtle nest temperatures

Abstract: There are major concerns about the ecological impact of extreme weather events. In the oceans, marine heatwaves (MHWs) are an increasing threat causing, for example, recent devastation to coral reefs around the world. We show that these impacts extend to adjacent terrestrial systems and could negatively affect the breeding of endangered species. We demonstrate that during an MHW that resulted in major coral bleaching and mortality in a large, remote marine protected area, anomalously warm temperatures also occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Additionally, we show that predictions of sand temperature using large‐scale records agree with those using local air temperature records at one of our study sites, that is, large‐scale proxies give a good indication of local conditions. This result agrees with the recent finding that broad‐scale environmental measurements can reflect local measurements (Hays et al, 2021). However, one important point to note is that the more local records – such as the air temperature records obtained from the airport used in our study – may not extend as far back in time as other large‐scale records, and so reconstruction of past sand temperatures will be limited.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, we show that predictions of sand temperature using large‐scale records agree with those using local air temperature records at one of our study sites, that is, large‐scale proxies give a good indication of local conditions. This result agrees with the recent finding that broad‐scale environmental measurements can reflect local measurements (Hays et al, 2021). However, one important point to note is that the more local records – such as the air temperature records obtained from the airport used in our study – may not extend as far back in time as other large‐scale records, and so reconstruction of past sand temperatures will be limited.…”
Section: Discussionsupporting
confidence: 93%
“…How to cite this article: Laloë, J.-O., Chivers, W. J., Esteban, N., & Hays, G. C. (2021). Reconstructing past thermal conditions in beach microclimates.…”
Section: Data Ava I L a B I L I T Y S Tat E M E N Tmentioning
confidence: 99%
See 1 more Smart Citation
“…the environment in which sea turtle eggs incubate. Previous work has shown that SST and air temperature (AT) measured over large scales near nesting sites are tightly correlated with sand temperature at nest depths [ 48 51 ]. More recently it was shown that the gradients of these relationships are consistent across sites, and that for every 1°C increase in AT, sand temperature at nest depth increases by an average 0.86°C (standard deviation = 0.26°C, n = 36; [ 52 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Ecologists can then use these open-source data to create models to address environmental questions about their focal taxon (e.g. [ 23 , 24 ]). Data from such sources can be accompanied by the deployment of in situ temperature loggers (electronic supplementary material, table S1).…”
Section: Introductionmentioning
confidence: 99%